High carbon steel/Inconel 718 bimetallic parts produced via Fused Filament Fabrication and Sintering (Fracture and Structural Integrity, 2023)
The possibility of producing high carbon steel/Inconel 718 bimetallic parts via Fused Filament Fabrication and Sintering is explored. Compatibility of the two alloys with particular attention to elements interdiffusion through the interface as well as the effect of the deposition strategy were analyzed. Microstructural features, relative density and parts shrinkage were investigated, as well. Although first-tentative process parameters values were not sufficient to reach an acceptable material densification, a good bonding between Inconel 718 and carbon steel was observed, suggesting the potential to obtain sound bimetallic parts with a great range of material properties. Due to a difference in densification kinetics, sintering temperature was revealed to be the most critical process parameter to optimize to minimize porosity.
Keywords: Additive Manufacturing; Fused Filament Fabrication; bimetallic material; Inconel 718; high carbon steel; microstructure; interdiffusion; defects